ASPEK KEPERCAYAAN DALAM PENERAPAN ILMU ADMINISTRASI BISNIS - Wayan Sugiartana (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2020)
This paper is focused to discuss in one aspect, namely aspects of trust in the application of business administration. Trust is a good gesture given by someone with the belief that someone has the trust to act and do something good for his business activities. In business building trust is very important. Some things happen that the complexity of the relationship in all matters related to aspects of trust, due to the reduced level of trust that is grown earlier. And if the aspect of trust is shown earlier, it can be trusted to run a business. For this, must be the actual position and what it is by stabilizing himself in the real situation.